Contamination level and human health hazard assessment of heavy metals and polycyclic aromatic hydrocarbons (PAHs) in street dust deposited in Mahshahr, southwest of Iran. Issue 8 (16th November 2016) - Rastegari Mehr, Meisam; Keshavarzi, Behnam; Moore, Farid; Sacchi, Elisa; Lahijanzadeh, Ahmad Reza; Eydivand, Simin; Jaafarzadeh, Nemat; Naserian, Siroos; Setti, Massimo; Rostami, Soqra
ABSTRACT: Mahshahr has a strategic position and is considered as industrial hub of Iran. Selected heavy metals and polycyclic aromatic hydrocarbons (PAHs) contamination and health risk, and the mineralogical composition of street dust from Mahshahr were investigated. Results indicated that geology is the main determinant of the dust mineralogical composition. Calculated enrichment factor (EF) and principal component analysis (PCA) showed that Pb, Hg, Zn, and Cu accumulations are greatly influenced by anthropogenic sources including traffic and industry. High heavy metals content poses great ecological risk in the study area and exposure doses revealed that ingestion is the main exposure route to street dust, especially for children in residential/commercial areas. It was found that the total amount of PAHs (∑PAHs) varies from 161 to 1996 µg/kg, dominated by four-ring PAHs. Diagnostic ratios and PCA showed that both petrogenic and pyrogenic sources of PAHs in Mahshahr street dust and traffic play important roles in this respect. Furthermore, toxic equivalents and incremental lifetime cancer risk of PAHs in street dust indicated a high potential carcinogenic risk for inhabitants mainly via dermal contact and ingestion pathways particularly for outdoor workers in industrial use scenario. Finally, distribution maps of total hazard index of heavy metals and cancer risk of PAHs indicated the most impacted zones for different groups and use scenarios.